Human Resources Management Dalam Program Eletronik Rencana Defenitif Kebutuhan Kelompok Tani Di Desa Bontomangngape Kabupaten Takalar - Ramadhani, Nur Fitra; Mappamiring, Mappamiring; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to find out how human resources management in the Electronic Program Defenitif Plan Needs of Farmer in Bontomangngape Village, Takalar Regency. This study used descriptive qualitative. The informants were 6 people. Data collection techniques were interview, observation, and documentation. Data analysis were data reduction , data presentation and verification. Teh result of this study showed that Human Resources Management in the Electronic Program Defenitive Plan for Farmer Group Needs in Bontomangngaoe Village, Takalar Regency was not optimal in this case from the aspect of the target, the estimated needs and the implementation was not quite enough because there were still varios factors such as not achieving the desired target, the needs had not been fulfilled, then ini the implementation of this program farmers still did not understand about the program, but the Planning stage it was quite good because it could be seen from the existence trainer who conducted training by farmers, then at the aggaran stage it was also quite good.